(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
The abundance of large and small impurities in cotton and the low efficiency of cotton cleaning and drying technology lead to low quality and high cost of the obtained cotton products. As a result, the prices of cotton products and the indicators of income and net profit are low. Accordingly, the development of new methods of cleaning raw cotton from impurities and resource-saving equipment and technologies with high productivity is one of the important tasks.